2015
DOI: 10.1016/j.schres.2014.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic pharmacological and chronic genetic NMDA receptor hypofunction differentially regulate the Akt signaling pathway and Arc expression in juvenile and adult mice

Abstract: NMDA receptor (NMDAR) hypofunction is a compelling hypothesis for the pathophysiology of schizophrenia, because in part, NMDAR antagonists cause symptoms in healthy adult subjects that resemble schizophrenia. Therefore, NMDAR antagonists have been used as a method to induce NMDAR hypofunction in animals as a pharmacological model of schizophrenia. Serine racemase-null mutant (SR−/−) mice display constitutive NMDAR hypofunction due to the lack of D-serine. SR−/− mice have deficits in tropomysin-related kinase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Although it is undoubtedly true that some of the non‐NMDA receptor actions contribute to the behavioural profile of each dissociative compound, there are compelling arguments supporting NMDA receptor antagonism as the likely major contributor to the psychotomimesis: There is a good correlation between potency of drugs, including between enantiomers, as NMDA receptor antagonists and their psychotomimetic effects in laboratory animals and to a limited extent in man (see above and Figures ). Competitive NMDA receptor antagonists share some behavioural effects with phencyclidine‐like compounds, including drug discrimination cues (Koek et al ., ; see Willetts et al ., for critical review), but more importantly have psychotomimetic effects in man (Grotta et al ., ; Herrling, ; Davis et al ., ; Muir, ). NMDA receptor antibodies have been implicated in the aetiology of some schizophrenias, although causality is unproven (Deakin et al ., ; Kayser and Dalmau, ; for reviews see Coutinho et al ., ; Pearlman and Najjar, ). Genetic risk factors for schizophrenia include several genes that impinge directly or indirectly on NMDA receptor function (Harrison and Weinberger, ; Gilmour et al ., ; Labrie et al ., ; Weickert et al ., ; Harrison, ). Genetic manipulations in mice affecting NMDA receptor activity induce (Belforte et al ., ; Labrie et al ., ; Wei et al ., ; Born et al ., ; Takagi et al ., ) or reduce (Hagino et al ., ; Yamamoto et al ., ) aspects of a schizophrenia‐like phenotype. Some clinical trials with drugs designed to up‐regulate NMDA receptor function have had positive outcomes (reviewed in Coyle, ). Other manipulations of glutamatergic transmission show promise in animal models and are being assessed therapeutically (reviewed in Javitt, and Dunlop and Brandon, ). Agonists of group II metabotropic glutamate receptors reduce hyperlocomotion induced by NMDA receptor antagonists in rats (Moghaddam and Adams, ; Cartmell et al ., ), ketamine‐induced cognitive deficits in man (Krystal et al ., ), and positive and negative symptoms of schizophrenia in man (Patil et al ., ).…”
Section: Ketamine Phencyclidine Schizophrenia and Nmda Receptor Antmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is undoubtedly true that some of the non‐NMDA receptor actions contribute to the behavioural profile of each dissociative compound, there are compelling arguments supporting NMDA receptor antagonism as the likely major contributor to the psychotomimesis: There is a good correlation between potency of drugs, including between enantiomers, as NMDA receptor antagonists and their psychotomimetic effects in laboratory animals and to a limited extent in man (see above and Figures ). Competitive NMDA receptor antagonists share some behavioural effects with phencyclidine‐like compounds, including drug discrimination cues (Koek et al ., ; see Willetts et al ., for critical review), but more importantly have psychotomimetic effects in man (Grotta et al ., ; Herrling, ; Davis et al ., ; Muir, ). NMDA receptor antibodies have been implicated in the aetiology of some schizophrenias, although causality is unproven (Deakin et al ., ; Kayser and Dalmau, ; for reviews see Coutinho et al ., ; Pearlman and Najjar, ). Genetic risk factors for schizophrenia include several genes that impinge directly or indirectly on NMDA receptor function (Harrison and Weinberger, ; Gilmour et al ., ; Labrie et al ., ; Weickert et al ., ; Harrison, ). Genetic manipulations in mice affecting NMDA receptor activity induce (Belforte et al ., ; Labrie et al ., ; Wei et al ., ; Born et al ., ; Takagi et al ., ) or reduce (Hagino et al ., ; Yamamoto et al ., ) aspects of a schizophrenia‐like phenotype. Some clinical trials with drugs designed to up‐regulate NMDA receptor function have had positive outcomes (reviewed in Coyle, ). Other manipulations of glutamatergic transmission show promise in animal models and are being assessed therapeutically (reviewed in Javitt, and Dunlop and Brandon, ). Agonists of group II metabotropic glutamate receptors reduce hyperlocomotion induced by NMDA receptor antagonists in rats (Moghaddam and Adams, ; Cartmell et al ., ), ketamine‐induced cognitive deficits in man (Krystal et al ., ), and positive and negative symptoms of schizophrenia in man (Patil et al ., ).…”
Section: Ketamine Phencyclidine Schizophrenia and Nmda Receptor Antmentioning
confidence: 99%
“…Genetic manipulations in mice affecting NMDA receptor activity induce (Belforte et al ., ; Labrie et al ., ; Wei et al ., ; Born et al ., ; Takagi et al ., ) or reduce (Hagino et al ., ; Yamamoto et al ., ) aspects of a schizophrenia‐like phenotype.…”
Section: Ketamine Phencyclidine Schizophrenia and Nmda Receptor Antmentioning
confidence: 99%
“…Again, deletions in a subset of genes belonging to the Arc complex were significantly enriched in patients with schizophrenia (Marshall et al, 2017 ). Finally, different mouse models relevant to schizophrenia show reduced Arc expression, which is instead not evident in mouse models relevant to other psychiatric disorders such as ADHD or bipolar disorders (Matsuo et al, 2009 ; Takao et al, 2013 ; Takagi et al, 2015 ; Managò et al, 2016 ; Chen et al, 2017 ; Mereu et al, 2017 ). This might suggest that the Arc pathway may serve as a hub that functionally links numerous schizophrenia risk-related factors.…”
Section: Arc Genetics In Schizophreniamentioning
confidence: 99%
“…Multiple genetic studies have identified Akt1 and Akt3 polymorphisms associated with schizophrenia, at least one of which is correlated with cognitive deficits (Blasi et al, 2011), and decreased levels of Akt and GSK3β have been found in postmortem brain samples from schizophrenic patients as well as in lymphocytes of schizophrenic patients (Beaulieu, 2012;Emamian, 2012;Emamian et al, 2004;Freyberg et al, 2010;Kozlovsky et al, 2002;Kozlovsky et al, 2004). In addition, transgenic mice with reduced Akt function display behavioral phenotypes reminiscent of those observed in schizophrenic subjects (Howell et al, 2017;Siuta et al, 2010), and Akt/GSK3 signaling abnormalities have been observed and correlated with cognitive deficits in several experimental systems used to study schizophrenia (Nadri et al, 2003;Takagi et al, 2015;Tamura et al, 2016;Willi et al, 2013). Biochemical studies have found that a number of currently prescribed antipsychotic drugs increase Akt phosphorylation in the striatum and prefrontal cortex in rodents (Roh et al, 2007;Sutton and Rushlow, 2011a), pointing to the Akt pathway as a potential target of antipsychotic action.…”
Section: Introductionmentioning
confidence: 99%